Analysis of the Company's Financial Performance Using the Du Pont System in the Building Construction Sub-Sector on the Indonesia Stock Exchange - Anggraini, Putri; Febrianty, Febrianty (Information Technology and Science (ITScience), 2022)
This study aims to determine the analysis of the financial performance of building sub-construction companies listed on the Indonesia Stock Exchange for the 2016-2020 period using the Du Pont System method. The Du Pont System includes the calculation of Net Profit Margin (NPM), Total Asset Turnover (TATO), Return On Investment (ROI), Equity Multiplier (EM) and Return On Equity (ROE). The research method used is a quantitative method with a descriptive approach and the data collection technique used is the company's annual report documentation technique. Based on the analysis and discussion, it can be seen that the Du Pont System analysis of building construction sub-sector companies listed on the Indonesia Stock Exchange for the 2016-2020 period shows a fairly good ROE performance, this is based on a comparison of industry standards. PT. Total Bangun Persada Tbk and PT. Wijaya Karya Bangunan Gedung Tbk is the company with the largest ROE, namely 18.37% and 17.18%, when compared to industry standards, these two companies are in very good condition. This indicates that the company is able to provide a very good return on the capital invested by the shareholders. The results of the research show that the average NPM ratio is in good condition which reflects the company can reduce costs so as to produce maximum profit. The average ratio of TATO and ROI shows a bad company condition that reflects the company's inefficient management of assets for sales and inefficient investment of assets. The results of the average EM show that the company's condition is quite good which reflects the company's efficiency in using its own capital to finance assets.